How to be a pirate (book 2)/. - Cowell, Criselda (New York : Little Brown and Company, 2004)
Follows the adventures and misadventures of Hiccup Horrendous Haddock the Third as his Vikings training continous and his father leads a stranger and the Hairy Hooligans to the Isle of Skullions in search of a pirate's treasure.
Keywords: Vikings- -- juvenile fiction; Dragons- -- fiction; Vikings- -- fiction; Humorous stories